The Role Of BPRS Metro Madani In Improving Islamic Financial Literacy And Inclusion In The Community Of Metro City - Anisa Fitria; Desi Wahyuni (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to analyze the role of BPRS Metro Madani in improving Islamic financial literacy and inclusion among the community of Metro City. This research uses a qualitative approach with a case study method. Data were collected through in-depth interviews, observation, and documentation involving operational managers, marketing staff, customer service, customers, and non-customers. Data were analyzed descriptively to understand the relationship between literacy, inclusion, and the role of BPRS. The results show that BPRS Metro Madani plays an important role in enhancing Islamic financial literacy through educational activities such as product socialization, contract explanation, and customer assistance. These efforts contribute to increasing public understanding and trust. However, Islamic financial literacy remains uneven, which affects the level of financial inclusion. While customers perceive positive benefits, such as business growth and income improvement, non-customers still prefer informal financial systems due to limited knowledge and trust. This study confirms that Islamic financial literacy acts as an intervening variable between the role of Islamic microfinance institutions and financial inclusion, especially in the context of BPRS at the local level. This study is limited to a single institution and qualitative approach, which may affect generalization. The findings imply the need for more intensive education and broader outreach strategies to improve literacy and inclusion.